Archival documents on Khakas resettlement to Uriankhai Territory in late 19th – early 20th centuries - Kotyusheva, Tatyana E. (The New Research of Tuva, 2020)
The article provides an overview of fonds and documents which contain information on resettlement of the Khakas to Uriankhai Territory (Tuva) in late 19th and early 20th century. The documents are preserved at the National Archives (prior to 07.04.2020 known as the State Archives) of the Republic of Tuva. They can be found in Fonds FR-123 “Head of Russian Settlement in Uriankhai”, FR-112 “Commissioner for the Affairs of Uriankhai Territory”, 870 “Civil Registry Office of the Republic of Tuva”, 357 “Mongush Bayan-oolovich Artas, Minister of the Interior, Tuvan ASSR”The resettlement of the indigenous population of Minusinsk Uezd to the Uriankhai Territory was a consequence of Stolypin’s land reform in 1906-1913. Since their native lands were now a desired target for Russian settlers, Khakases, along with some of the Russian farmers, continued further to Tuva. They settled densely around Russian trade posts along the valleys of the rivers Khemchik and Shagonar, as well as in the south of Tuva. Their main occupations were cattle breeding, grain husbandry, and sometimes trade and breeding Siberian red deer (maral).Archival documents include names, ages, occupations and places of residence of each family member. This allowed us to identify 68 households (327 individuals all in all) as of early 1916. Birth registers contain data on birth rate and names of the newborn.Settling on new lands did not come easily. The archives contain documents of the court which reveal the complex relations between the Khakas and local Russian authorities. However, the similarity of language, culture, lifestyle and housekeeping between Tuvans and the Khakas made adaptation easier for the latter, sometimes even to the level of assimilation. For instance, archival sources revealed the Khakas roots of Mongush Bayan-oolovich Artas, Minister of the Interior of Tuvan Autonomous Oblast (1913-1994).
Keywords: archive; archival documents; Uriankhai Territory; Tuva; history of Tuva; Tuvans; Khakas; Minusinsk Uezd; Stolypin reform; State Archives of the Republic of Tuva; National Archives of the Republic of Tuva